Nilai-Nilai Living Qur’an dalam Tradisi Sadakah Kaji Kamatian di Nagari Lareh Nan Panjang Selatan - Ilmi, Ghaniyatul; Fata, Azamel; Andika, Erwin Saputra; Fitri, Aulia (Al-Kauniyah, 2025)
The sadakah kaji kamatian tradition in Nagari Lareh Nan Panjang Selatan is a Minangkabau cultural-religious practice that integrates local customs with Islamic teachings. This tradition includes the recitation of Qur’anic verses, zikir, collective prayers, and charitable giving, all of which are understood as expressions of Qur’anic values and forms of social solidarity. The community regards this tradition as an act of worship, a means of strengthening family ties, and a reminder of death, making it an essential part of Living Qur’an practices in daily life. This study employs a qualitative method with phenomenological and anthropological approaches. Data were collected through observation, interviews, and documentation, and validated using triangulation. The findings show that this tradition embodies values of worship, charity, social bonding, spiritual education, and cultural transmission to the younger generation. The sadakah kaji kamatian tradition demonstrates that the values of the Qur’an are not only recited but also manifested in the social practices of Minangkabau society.